The Design and Psychometric Properties of a Peer Observation Tool for Use in LMS-Based Classrooms in Medical Sciences - Mirmoghtadaie, Zohrehsadat; Keshavarz, Mohsen; Mohammadimehr, Mojgan; Rasouli, Davood (International Review of Research in Open and Distributed Learning, 2023)
In peer observation of teaching, an experienced colleague in the educational environment of a faculty member observes the educational performance of that faculty member and provides appropriate feedback. The use of peer review as an alternative source of evidence of teaching effectiveness is increasing. However, no research has been done in the field of tool design and development to peer review in classrooms that use a learning management system (LMS). This study used mixed methods. In the qualitative stage, after studying sources and interviewing professors active in virtual education, a question bank was prepared and a 26-item initial questionnaire created. In the quantitative stage, the psychometric properties of the developed instruments, such as the face, content, and structural validity, were examined, and reliability tests were performed. IBM SPSS Statistics (Version 20) was used for analysis. Five categories, including content preparation, content presentation, effective interactions, motivation management, and support services, and 26 subcategories were determined to be effective indicators in peer observation in LMS-based classes in medical sciences. During content analysis, 9 items were removed due to lack of necessary criteria. Then, using principal component analysis and varimax rotation in the present mode )Watkins, 2018), 5 components with eigenvalues ​​higher than 1 were extracted, which explained a total of 70.55% of the total variance. The inter-cluster correlation coefficient (ICC) was 0.88. Thus, the peer observation measurement tool, designed with 17 expressions using the answer method “yes/no”, showed good validity and reliability. The research results demonstrate that the evaluation of virtual classes of professors by their peers is effective and that the results can be used in e-learning promotion plans.